(untitled) (Journal of Asian Development Studies, 2017)
Education helps to reduce the poverty by increasing the job opportunities and by increasing the productivity of labor. By providing the equitable quality education the long life learning opportunities can be provided to all. GDP Per capita is used as a proxy for measuring the poverty and education, life expectancy, labor force Participation rate, income inequality and female education is taken as independent variables. This study investigates the impact of education and income inequality on poverty of Pakistan by applying Autoregressive Distributive Lag (ARDL) approach of co-integration for the period 1985-2014. The findings of the study show that increase in education worsens poverty of Pakistan in the long run. The positive sign and significance of coefficient of income inequality also confirms long run relationship between income inequality and poverty in Pakistan.